Surgical Considerations of One-Stage Reconstruction of Large Extremity Defects Using a Thin Deep Inferior Epigastric Perforator Flap - Seung Yeol Lee; Moon Chul Seok; Bo Young Park (Archives of Plastic Surgery, 2023)
Background One-stage reconstruction with “thin perforator flaps” has been attempted to salvage limbs and restore function. The deep inferior epigastric perforator (DIEP) flap is a commonly utilized flap in breast reconstruction (BR). The purpose of this study is to present the versatility of DIEP flaps for the reconstruction of large defects of the extremities.